Kualitas Hidup Pasien ODGJ dalam Proses Recovery yang Menjalani Terapi Okupasi Hortikultural di Wilayah Kerja Puskesmas Kota Timur - Ariani, Gusti Ayu Putri (UKInstitute, 2024)
The prevalence of People with Mental Disorders in Gorontalo Province reaches 0.15% of the total population of 1,804 people. This amount is an accumulation of people with mental disorders in the City and District of Gorontalo Province covering mild to severe mental disorders. Mental disorders do not only have an impact on individual therapy but also on the patient's family and community. Mental patients in the recovery process are also difficult to accept in the community, this can reduce the patient's quality of life. Horticultural occupational therapy is one of the therapies that can be given to patients in the recovery period. Objective: To describe the quality of life of patients with mental disorders in the recovery process after being given horticultural occupational therapy. Methodology: This study uses a qualitative descriptive phenomenology design using through indepth interviews for the quality of life of mentally disturbed patients in the recovery process after being given hortucultural occupational therapy. Results: The results of the study found three themes consist became physically active, being motivated and hope for being productive and need family support. Conclusion: Horticultural occupational therapy can improve the quality of life of patients with mental disorders in the recovery process.